Americanization of Mexican law : non-trade issues in the North American Free Trade Agreement. - ZAMORA, Stephen (1993)
Discusses the principal non-trade issues that have been addressed in NAFTA, and related issues that have been discussed in parallel bilateral negotiations between US and Mexican government officials. Considers the importance that cultural perspectives play in addressing non-trade issues in the context of NAFTA.